2005
DOI: 10.1007/bf02850183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prehospital emergency care in the field and during the ambulance drive to the hospital

Abstract: This study was conducted to evaluate the appropriateness of ambulance procedures and interventions in the management of patients dispatched to 2 emergency departments (EDs) of urban hospitals in Izmir. Use of trauma boards and cervical collars, airway patency, breathing, and circulation problems were recorded in both EDs. Eighty-one patients with a mean age of 47.54 +/- 2.36 years (range, 4-89) brought into the ED via ambulances were enrolled in the study. Airway maneuvers were performed in patients with airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Using a cervical collar and back boards (57.73%, 59.05%) were the items not used despite its necessity. In Soysal's study in Turkey, 6 of 30 (20%) had used a cervical collar [ 15 ]. In a study performed by Armstrong, spinal fixation was not performed in more than 8% of patients with spinal cord injuries [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a cervical collar and back boards (57.73%, 59.05%) were the items not used despite its necessity. In Soysal's study in Turkey, 6 of 30 (20%) had used a cervical collar [ 15 ]. In a study performed by Armstrong, spinal fixation was not performed in more than 8% of patients with spinal cord injuries [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been found that current pre-hospital emergency care is somehow inadequate. Increasing the quality of pre-hospital care and knowledge, promoting awareness and higher education in EMS staff are suggested accordingly [ 14 , 15 ]. In fact, the purpose of treatment interventions and improving the personnel's knowledge is to decrease mortality and disability.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Ambulansla hastaneye getirilen hastaların değerlendirildiği başka bir çalışma, ambulansta yapılan müdahalelerin yetersizliğini ortaya koyması bakımından dikkat çekicidir. 10 Türkan ve Tuğcu'nun yaptığı acil servislerde tıbbi uygulama hatalarının incelendiği araştırmada 112 olgudan 55'inde hatalı uygulamaların olduğunu tespit edilmiştir. 11 Bu iki çalışma, bu dönemde acil sağlık hizmetlerinin durumunu göstermesi açısından önemlidir.…”
Section: Discussionunclassified
“…Soysal ve ark.nın yaptıkları çalışmaya katılan hekimlerin %91'i (n=53), hastane öncesinde çalışan sağlık personelinin verdiği sağlık hizmetinin denetim ve değerlendirilmesini, acil tıp uzmanlarının danışman olarak çalışmaları gerektiğini belirtmişlerdir. 21 Paramediklerin %65,7'si video kamera sisteminin telefonla danışmadan daha faydalı olduğunu düşünmektedir. Capampangan ve ark.…”
Section: Gereç Ve Yöntemlerunclassified